1986
DOI: 10.1007/bf01869681
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of anion-cation selectivity of amphotericin B channels

Abstract: Zero current potential and conductance of ionic channels formed by polyene antibiotic amphotericin B in a lipid bilayer were studied in various electrolyte solutions. Nonpermeant magnesium and sulphate ions were used to independently vary the concentration of monovalent anions and cations as well as to maintain the high ionic strength of the two solutions separated by the membrane. Under certain conditions the channels select very strongly for anions over cations. They are permeable to small inorganic anions. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

1988
1988
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(32 citation statements)
references
References 9 publications
1
31
0
Order By: Relevance
“…The addition to the membrane bathing solution of phloretin, which is known to decrease the membrane dipole potential [23], [24], produced a significant decrease of the channel conductance (by factor of 3), while the pore conductance increased by ∼1.5 in the presence of RH 421, known to increase ϕ d [25]. For preferentially anion-conductive AmB-channels [26] one could expect that a decrease of ϕ d would produce a decrease of the pore conductance [23], [27]. We have previously observed similar effects of these dipole modifiers on predominantly anion-selective syringomycin E channels [28].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The addition to the membrane bathing solution of phloretin, which is known to decrease the membrane dipole potential [23], [24], produced a significant decrease of the channel conductance (by factor of 3), while the pore conductance increased by ∼1.5 in the presence of RH 421, known to increase ϕ d [25]. For preferentially anion-conductive AmB-channels [26] one could expect that a decrease of ϕ d would produce a decrease of the pore conductance [23], [27]. We have previously observed similar effects of these dipole modifiers on predominantly anion-selective syringomycin E channels [28].…”
Section: Resultsmentioning
confidence: 99%
“…The exact molecular architecture of the AmB channel is under debate; different models for the formation and structure of the AmB channel have been proposed. The most popular is the sterol-dependent double-pore model: the two-sided effect of polyene antibiotic results from the association of AmB with sterol molecules and the formation of anion-selective symmetric barrel stave pores made from two “half-pores” in opposite monolayers [3][6].…”
Section: Introductionmentioning
confidence: 99%
“…Metabolic disruption and cell death are consequent upon membrane alterations. Investigations of the sterol content of mutant strains of Candida albicans and Cryptococcus neoformans has demonstrated that resistance is often associated with alterations in membrane sterol composition (7,21,22 (11)(12)(13)(14)(15)(16)(17)(18)(19) . Resistance to amphotericin B is rare, but is noteworthy for Pesudallescheria boydii, Fusarium spp, and Trichosporon spp.…”
Section: Amphotericin Bmentioning
confidence: 99%
“…A major advance in the use of this agent has resulted from an understanding of the mechanism of its renal toxicity, which is presumed to involve tubuloglomerular feedback. The suppression of glomerular filtration could be reduced by administering sodium chloride (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22).…”
Section: Amphotericin Bmentioning
confidence: 99%
“…noted also in certain other channels that allow both cation and anion entry ( Borisova et al, 1986 ;Franciolini and Nonner, 1994a,b ).…”
Section: What Difference Does It Make For Cell Signaling?mentioning
confidence: 99%